The efficacy of the traditional Chinese medicine Jia Wei Niu Bang Zi granule combined with methotrexate in treating active rheumatoid arthritis: A multicenter, randomized, double-blinded controlled clinical trial. Issue 6 (February 2019) - Wang, Yi-Ru; Liu, Li; Wang, Xiao-Yun; Wang, Qiong; Yao, Min; Cui, Xue-jun; Mao, Jian-Chun; Liu, Jian; Gu, Xiao-Hua; Chen, Yong-Li; Yu, Xiang; Shi, Qi; et al.
Abstract: Background: Rheumatoid arthritis (RA) is a chronic systemic and autoimmune inflammatory disease ending with the destruction of joints. Current therapies can relieve RA symptoms, but some also bring severe adverse events. Therefore, an effective and safe therapeutic strategy remains to be created to benefit patients with RA by large. Jia Wei Niu Bang Zi granule (NBZG) consisting of RA-fighting Chinese herbals has been used in Longhua Hospital in the last several decades. NBZG has potential therapeutic effect on RA, which should be evaluated by larger sample clinical trial. Methods: A multicenter, randomized, double-blind, placebo-controlled clinical trials will be conducted to determine the efficiency of NBZG in pain relief and joint protection. A total of 120 patients with active RA will be enrolled, and treated with NBZG or placebo for 12 weeks. The primary outcome measurements include rate of American College of Rheumatology (ACR) 50 at 12 weeks' treatment. The 2nd outcome measurements include rate change of ACR20, ACR70, the disease activity score (DAS) 28, 36-item Short-Form Health Survey Questionnaire, Health Assessment Questionnaire - Disability Index, score changes of Patient Assessment of Arthritis Pain, Patient Global Assessment of Arthritis, and the Athens insomnia scale at the same time points. Discussion: Although NBZG has shown efficacy in treating RA in Longhua Hospital for decades, the universality of this efficacy needs evaluated. The results of this trial will provide a convincing evidence about NBZG's efficacy in treating active RA in a large population. Trial registration: ClinicalTrials.gov ID: NCT03173040 (registered on May 30, 2017)